"There's No Flies at Noonkanbah but the Scabs Are on the Way": Trade Union Support for Aboriginal Rights during the Noonkanbah Dispute, 1979–80. (1st May 2016) - Vassiley, Alexis
Abstract : In the late 1970s the Noonkanbah Aboriginal community in the Kimberley region of Western Australia took a determined stand against oil exploration on their land. The exploration was to be carried out by a US-based multinational, and had been approved by the Liberal government of Charles Court. The campaign found many allies, including the trade union movement. Trade union support included an official Australian Council of Trade Unions (ACTU) and Trades and Labor Council of Western Australia (TLC) ban placed on drilling for oil which was actively supported by members of the Transport Workers' Union (TWU) and Australian Workers' Union (AWU), who refused to transport cargo and drill for oil respectively. This case study of union industrial action taken in support Aboriginal rights has not been adequately documented or analysed. The evidence shows that important preconditions for this labour movement contribution were a high level of industrial militancy and confidence among unions, and political leadership from some activists within the movement who supported a broader agenda of social change.